Aspectos gerais da coinfecção leishmaniose Visceral / HIV, no Maranhão - LIMA, Uiara Regina Silva de (2018)
Introduction: The leishmaniasis are diseases caused by a protozoan of the genus Leishmania, presenting two types of clinical manifestation: American Cutaneous Leishmaniose (ACL) and Visceral Leishmaniasis (VL), the further being caused mainly by the species Leishmania infantum chagasi, present in several regions of Brazil. It is transmitted by the bite of Phlebotomine (sandfly) females infected by Lutzomyia longipalpis, predominant in wild areas, but with a frequency increase in urban areas, including the peripheries of cities. Visceral Leishmaniasis (VL) has different clinical manifestations, it may cause death if not treated properly. The clinical scenario of VL can be aggravated if combined with immunosuppressive disease such as infection by HIV (Human Immunodeficiency Virus). The Acquired Immunodeficiency Syndrome (AIDS) is a big public health issue, with evident expansion of it to medium and small countryside municipalities of the country, causing a crossing with VL, which expands in the opposite direction, leading to an increase in the number of co-infections VL/HIV. Objective: Therefore, this study aims at analyzing the clinic-epidemiologic, therapeutic and evolutive profile of co-infection VL/HIV positive, comparing with VL/HIV negative, from 2007 to 2017. Results: A total of 133 positive VL/HIV and 37 negative VL/HIV were identified. Of those in the co-infected group, 89.15% (115) were male, with prevalence in the 30 to 39 age group. The majority in both groups (co-infected and not co-infected) lives in the countryside, 57.1% of the VL/HIV and 79.3% for the VL. Regarding the clinical complains observed in the patient’s admission, most of it reported by Visceral Leishmaniosis without HIV, fever and hair loss were statistically significant. Likewise, in the physical exam for admission, patients with VL not co-infected with HIV presented most of the alterations, the occurrence of weight loss, fever, jaundice, hepatomegaly and splenomegaly were noticed, and dyspnea was the only exception, present only in co-infected patients, in 13.5% (17) of the cases. The HIV diagnosis preceded the Visceral Leishmaniosis diagnosis in 2.6 years (p<0.001). Laboratory alterations did not present differences between groups, excepting lymphopenia present in 23.8% of the HIV/VL co-infected patients. Visceral Leishmaniosis, on the other hand, presented significant alterations in the transaminases rates, with an 73% increase of AST and 57.3% ALT. The treatment used in the co-infected group was mainly liposomal amphotericin B, yet in the Visceral Leishmaniosis N-methylglucamine antimonate was use (Sbv)(p<0.001). Recurrence and death were observed only in cases of co-infection with 38.3% (51) and 10.5% (14), respectively. Fever was the associated factor to recurrence and death, and for death were find associated factors and recurrence (p=0.029) weight loss (p=0.044), urea (p=0.029) and creatinine (p=0.042). Conclusion: The leishmaniasis associated to HIV was presented with several clinical symptomatology, not showing, most of the times, the classic observed in isolated Visceral Leishmaniosis, fever, pancytopenia and hepatosplenomegaly. The Visceral Leishmaniosis and HIV co-infection was the only syndrome which evolved with recurrence and death, being necessary to know the risk factors present in the interaction to reduction of this outcome.